Prevalence and antimicrobial resistance profile of bacterial foodborne pathogens in Nile tilapia fish (Oreochromis niloticus) at points of retail sale in Nairobi, Kenya - Mumbo, Millicent T.; Nyaboga, Evans N.; Kinyua, Johnson; Muge, Edward K.; Mathenge, Scholastica G. K.; Muriira, Geoffrey; Rotich, Henry; Njiraini, Bernard; Njiru, Joshua M. (Frontiers in Antibiotics, 2023)
Proteus spp., Staphylococcus spp., Pseudeomonas spp., and pathogenic Vibrios are among the major foodborne pathogens associated with the consumption of contaminated fish. The increasing occurrence of antimicrobial resistance in these pathogens is a serious public health concern globally and therefore continuous monitoring of antimicrobial resistance of these bacteria along the food chain is crucial for for control of foodborne illnesses. The aim of this study was to assess the prevalence, antimicrobial resistance patterns, antibiotic resistance genes, and genetic diversity of bacterial foodborne pathogens recovered from fresh Nile tilapia (Oreochromis niloticus) obtained from retail markets in Nairobi, Kenya. A total of 68 O. niloticus fish with an average weight of 300.12 ± 25.66 g and body length of 23.00 ± 0.82 cm were randomly sampled from retail markets and tested for the presence of Proteus, Staphylococcus aureus, Pseudomonas aeruginosa, Vibrio cholerae, and Vibrio parahaemolyticus. Standard culture-based microbiological and Kirby–Bauer agar disk diffusion methods were used to isolate and determine the antimicrobial resistance patterns of the isolates to 11 selected antibiotics. Statistical analysis was performed using Minitab v17.1, with p < 0.05 considered significant. The genetic diversity of the multidrug-resistant (MDR) and extensively drug-resistant (XDR) bacteria was determined using 16S rRNA sequencing and phylogenetic analysis, and polymerase chain reaction (PCR) was used for detection of antibiotic resistance genes in MDR bacterial isolates. High levels of bacterial contamination were detected in fresh O. niloticus fish (44/68, 64.71%). The most prevalent bacteria were Proteus spp. (44.12%), with the rest of the bacterial species registering a prevalence of 10.29%, 4.41%, 2.94%, and 2.94% (for S. aureus, P. aeruginosa, V. cholerae, and V. parahaemolyticus, respectively). Antimicrobial resistance was detected in all the bacteria species and all the isolates were resistant to at least one antibiotic except cefepime (30 µg). Additionally, 86.36% of the isolates exhibited multidrug resistance, with higher multiple antibiotic resistance indices (MAR index >0.3) indicating that fresh O. niloticus fish were highly contaminated with MDR bacteria. Results of 16S rRNA sequences, BLASTn analysis, and phylogenetic trees confirmed the identified MDR bacterial isolates as Proteus mirabilis and other Proteus spp., S. aureus, P. aeruginosa, V. cholerae, and V. parahaemolyticus. PCR analysis confirmed the presence of multiple antibiotic resistance genes blaTEM-1, blaCMY-2, tetA, tetC, Sul2, dfrA7, strA, and aadA belonging to β-lactamases, tetracycline, sulfonamide, trimethoprim, and aminoglycosides in all the MDR bacterial isolates. There was strong correlation between antibiotic- resistant genes and phenotypic resistance to antibiotics of MDR bacteria. This study showed high prevalence of multidrug resistance among foodborne bacterial isolates from fresh O. niloticus fish obtained from retail markets. From this study, we conclude that fresh O. niloticus fish are a potential source of MDR bacteria, which could be a major risk to public health as a consequence of their dissemination along the human food chain. These results highlight the prevalence of antimicrobial-resistant foodborne pathogens in fish purchased from retail markets and underscore the risk associated with improper handling of fish.